2020
DOI: 10.13057/biodiv/d211126
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and rumen fermentation profile of mangrove leaves (Avicennia marina) from West Sumatra, Indonesia

Abstract: Abstract. Jamarun N, Pazla R, Arief, Jayanegara A, Yanti G. 2020. Chemical composition and rumen fermentation profile of mangrove leaves (Avicennia marina) from West Sumatra, Indonesia. Biodiversitas 21: 5230-5236. This study aimed to determine the potential of mangrove leaves of Avicennia marina for ruminant animal feed. Laboratory tests were carried out on A. marina with three replicates. Parameters measured were proximate and fiber contents, rumen fluid profile (pH, NH3 and VFA), digestibility of nutrients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
(18 reference statements)
1
16
1
Order By: Relevance
“…The higher CP concentration for A. marina leaves from this study is might be due to either genotypic potential of tree to fix atmospheric nitrogen and accumulate high content of nutrients which is required for optimum growth and accumulation of more nitrogen in their leaves. The CP concentration of A. marina leaves in this study was higher than reported value of (133g/kg, DM) by [27], (110.4g/kg, DM) by [28] and (151.4g/kg, DM) by [29]. The crude protein of A. seyal leaves in this study was lower than reported value of (169.6g/kg, DM) by [30] from Ethiopia.…”
Section: Chemical Compositioncontrasting
confidence: 80%
“…The higher CP concentration for A. marina leaves from this study is might be due to either genotypic potential of tree to fix atmospheric nitrogen and accumulate high content of nutrients which is required for optimum growth and accumulation of more nitrogen in their leaves. The CP concentration of A. marina leaves in this study was higher than reported value of (133g/kg, DM) by [27], (110.4g/kg, DM) by [28] and (151.4g/kg, DM) by [29]. The crude protein of A. seyal leaves in this study was lower than reported value of (169.6g/kg, DM) by [30] from Ethiopia.…”
Section: Chemical Compositioncontrasting
confidence: 80%
“…Furthermore, high protein content is probably due to an increase in the number of mold cells (Nasseri et al, 2011;Cairns et al, 2019). Crude fiber consists of cellulose, hemicellulose, lignin, and silica, where the content is influenced by age as well as the species of plants (Jamarun et al, 2020). The fermentation process reduced the value of crude fiber in all treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Based on Table 2 below, it can be seen that the fermentation process that occurs in the rumen with the addition of P and S minerals with different doses of ammoniated PLF has been going well with indications of pH values in all treatments in the range of 6.58 to 6.87. This value is still within the normal range (6-7) for microbial growth, development and microbial activity (Church, 1988;Erdman, 1988;Jamarun et al, 2020;Riestanti et al, 2021;Jamarun et al, 2017a) reported that the optimal pH value for the digestibility of the fiber fraction from fermented PLF is 6.74-6.76. The pH value of fermented PLF supplemented with minerals P, Mg and S is 6.80-6.88 (Febrina et al, 2016a).…”
Section: Rumen Fluid Characteristicsmentioning
confidence: 89%
“…In the Dhamasraya area, there are still few who use this garden waste as animal feed. Generally, farmers are more familiar with palm kernel cake as concentrate feed (Jamarun et al, 2020;Arief et al, 2020). Ruminants such as cows, buffaloes, goats and deer have advantages in their digestive organs that can digest low-quality forages such as PLF.…”
Section: Introductionmentioning
confidence: 99%